2007
DOI: 10.1902/jop.2007.070090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 0.12% Chlorhexidine Gluconate Rinsing on Previously Plaque‐Free and Plaque‐Covered Surfaces: A Randomized, Controlled Clinical Trial

Abstract: A 0.12% CHX gluconate mouthrinse had little antiplaque and antigingivitis effect on previously plaque-covered surfaces. These results confirm the diminished effect of CHX on structured biofilm and reinforce the necessity of biofilm disruption before the initiation of CHX mouthrinse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 69 publications
5
40
0
1
Order By: Relevance
“…Clinical trials utilizing experimental gingivitis models have been frequently used as a short-term model to evaluate the antiplaque and antigingivitis efficacy of mouthrinses containing antimicrobial agents. These trials have tested a fixed combination of essential oils, 8,9 0.12% chlorhexidine gluconate, 25,26 cetylpyridinium chloride, 27 0.1% hexetidine, 28 and other noncommercial antimicrobial agents. 29 Therefore, there is enough evidence to support that experimental gingivitis study designs, like long-term models, have been accepted as a valid model to determine and compare efficacy of antiseptic mouthrinses.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials utilizing experimental gingivitis models have been frequently used as a short-term model to evaluate the antiplaque and antigingivitis efficacy of mouthrinses containing antimicrobial agents. These trials have tested a fixed combination of essential oils, 8,9 0.12% chlorhexidine gluconate, 25,26 cetylpyridinium chloride, 27 0.1% hexetidine, 28 and other noncommercial antimicrobial agents. 29 Therefore, there is enough evidence to support that experimental gingivitis study designs, like long-term models, have been accepted as a valid model to determine and compare efficacy of antiseptic mouthrinses.…”
Section: Discussionmentioning
confidence: 99%
“…This was also supported by the greater efficacy of CHX compared to the green tea extract on both the buccal and palatal ES. However, 0.12% CHX has limited efficacy in the deeper layers of an established biofilmed compared to planktonic cultures 6 , and this reduced action against an established biofilm seems to be clinically important regarding gingivitis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect was also demonstrated in the field of full dentures. [22][23][24] The time effect on biofilm accumulation over the study period (Figure 7) demonstrated that each of the CHX or VBC hygienic protocols provided a fairly constant level of biofilm prevention over the 70 days of measurement (five consecutive aligners). That is, gradual deterioration in aligner maintenance over time did not occur.…”
Section: In Vitro Clinical Studymentioning
confidence: 99%